Kandungan Protein dan Kalsium Pada Biskuit Formula Tempe dengan Penambahan Tepung Daun Kelor (Moringa oleifera) Sebagai Makanan Pendamping ASI (MP-ASI) - Tri Suhartini; Zakaria Zakaria; Asmarudin Pakhri; Mustamin Mustamin (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
The results of the research on tempe biscuit with the substitution of moringa flour as MP-ASI did not reveal the content of protein and calcium which is a nutrient Which is important to know as fast food. This study aims to determine the content of protein and calcium in tempe biscuit formula with kelor leaf flour substitution.This research uses laboratory. Samples analyzed were 2 samples with no substitution of 0% Moringa flour (control) and samples with Moringa flour substitution 9% (13.5 g) based on consumer acceptance. Aanalysis of proteins by khjedal method and mineral by atomic analysis spektrofothometer (AAS). The results showed that the content of protein and calcium biscuit of tempe formula with the substitution of maize flour 9% (13.5 g) respectively by 14.9% and 38.3 mg, Greater than non-substitution of maize leaf powder respectively 12.6% and 21.4 g. It was concluded that the content of protein and calcium biscuit with the substitution of moringa flour is higher than that without the substitution of moringa flour. Further research on the formulation of complementari of food for breast milk is required to balance the nutritional value in accordance with the needs of infants 6-24 months. Keywords : Biscuits, Protein Content, Calcium Conten